Conceptualizing Pornographication: A Lack of Clarity and Problems for Feminist Analysis - Tyler, Meagan; Quek, Kaye (Sexualization, Media, & Society, 2016)
The mainstreaming of pornography, often referred to as pornographication, pornification, or porn-chic, has become a topic of considerable academic and popular interest. In the last 15 years, an expanding academic literature has documented and begun to analyze the increasing consumption and normalization of pornography as well as pornographic imagery. More recently, there has also been a growing concern among policymakers and commentators in the mainstream media about trends labeled “sexualization” and, in particular, the potential consequences of these trends for children. This article begins by sketching out the academic origins of “pornographication” and related terms before considering the different ways that prominent authors have conceptualized them. Recent literature on sexualization is then outlined, with a focus on understanding this in the context of discussions around pornographication. Using a number of examples from key academic texts, and from prominent print media outlets in Australia, we argue that there is a lack of conceptual clarity about pornographication and that pornographication is often conflated with sexualization. We suggest that the lack of clarity in existing literature creates two key issues for feminist analysis: (1) it obscures the role of the pornography industry in the processes of pornographication and (2) it deflects discussion away from the potential harms of the normalization of pornography and pornographic imagery for adult women. It is, therefore, important to clarify and separate the terminology of pornographication and sexualization in order to further critical feminist analyses of these cultural trends.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; cours; discipline; discours dominant; pornographie; premier cycle; périodes historiques; sciences humaines; sciences sociales; sex1911; sexualité; systèmes d'oppressions; thématiques; violences

Mon corps a-t-il un sexe? Sur le genre, dialogues entre biologies et sciences sociales - Gonthier, Josiane; Ruppli-Coursange, Mireille (La Découverte, 2015)
"Sexe" est l'un des mots de la langue française que les gens sans distinction de classe, de religion, d'apparence ou de profession, utilisent avec grand intérêt, qu'ils soient accoudés au zinc d'un bistrot ou à la paillasse d'un laboratoire de biologie moléculaire. Deux mises en scène distinctes, sociale ou scientifique ; deux scénarios différents : d'un côté, les histoires d'amour ou d'imaginaire sexuel, de l'autre, les recherches biologiques. Sous ce mot de "sexe", notre langue, si riche, produit une polysémie bien fâcheuse. L'ambition de ce volume, qui rassemble les contributions de chercheurs et chercheuses en sciences de la vie et en sciences humaines et sociales est de faire le point sur les connaissances concernant le sexe biologique et ses variations, dont on sait désormais qu'il ne permet pas de séparer les individus en deux catégories bien distinctes. Ce livre veut aussi évaluer l'impact du genre sur le développement du corps des êtres sexués et sur la construction de leur identité. Enfin, il cherche à apprécier dans quelle mesure les croyances liées au genre (bicatégorisation mâle-femelle stricte, supériorité masculine) ont pu influencer les recherches menées sur le sexe biologique. Et les témoignages de personnes intersexes et transgenres apportent sur la question de l'identité sexuée un éclairage complémentaire qui bouscule les "réponses" que donnent le plus souvent la médecine et le droit.
Section: 1 vol. (358 p. - [32] p. de pl.) : ill. en noir et en coul. ; 24 cm.
Keywords: approches et analyses; biologie; corps; cours; discipline; discours dominant; premier cycle; psy4910; psychologie; pédagogie; queer; sciences; sciences humaines; sciences sociales; sexualité; systèmes d'oppressions; thématiques; épistémologie; études de genres

Des femmes respectables : classe et genre en milieu populaire - Skeggs, Beverley (Agone, 2015)
La matière première de ce livre est une série d'entretiens menés par Beverley Skeggs avec quatre-vingt-trois jeunes femmes issues de la classe ouvrière anglaise, inscrites à une formation d'aide à la personne et travaillées par leur propre respectabilité. Abordant leur rapport à la sexualité, à la classe ou au féminisme, cet ouvrage vient apporter un prolongement essentiel aux travaux de Pierre Bourdieu et de Paul Willis.
Édition originale : B. Skeggs, Formations of Class & Gender. Becoming Respectable, Sage, 1997
Keywords: 1900-1999; 1980-1989; 1990-1999; analyse de discours; angleterre; approches et analyses; care; classe ouvrière; classe sociale; cours; cultural studies; cycles supérieurs; discipline; ethnographie; europe; fem7000; fémininité; féminisme marxiste; histoire et politique; point de vue situé; périodes historiques; rapports sociaux de sexe; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; sciences sociales; sexualité; sociologie; thématiques; épistémologie

Rethinking the effects paradigm in porn studies - McNair, Brian (Porn Studies, 2014)
It has been an assumption of most anti-pornography discourse that porn damages women (and children) in a variety of ways. In Porno? Chic!, the author interrogated this assumption by examining the correlation between the incidence of sexual violence and other indicators of misogyny, and the availability and accessibility of pornography within a number of societies. This article develops that work with a specific focus on the regulatory environment as it relates to pornography and sexual representation. Does a liberal regulatory regime in sexual culture correlate with a relatively advanced state of sexual politics in a given country? Conversely, does an illiberal regime, where pornography and other forms of sexual culture are banned or severely restricted, correlate with relatively strong patriarchal structures? A comparative cross-country analysis seeks to explain the correlations identified, and to assess the extent to which the availability of porn can be viewed as a causal or a consequential characteristic of those societies where feminism has achieved significant advances.
Keywords: LGBTQIA2+; analyse comparée; approches et analyses; communication; corps; cours; discipline; droits des femmes*; féminisme pop; histoire et politique; identités LGBTQIA2+; premier cycle; ressource en ligne; sciences humaines; sciences sociales; sex1911; sexualité; thématiques; violences; études culturelles

Sociologie de l'homosexualité - Chauvin, Sébastien; Lerch, Arnaud (La Découverte, 2013)
Cet ouvrage s'inscrit dans le foisonnement de la sociologie du genre et des études gaies et lesbiennes. Il propose une synthèse des recherches en sciences sociales sur l'homosexualité en France et dans le monde. Nourri des apports de la réflexion théorique et de la critique historique, il donne à voir la diversité des figures de la dissidence sexuelle selon les périodes, les milieux sociaux et les aires culturelles, et la façon dont celle-ci interroge les constructions contemporaines de l'hétérosexualité. Des inscriptions territoriales aux trajectoires sociales, des styles de vie aux mobilisations politiques, des codes langagiers aux modes de consommation, les multiples traits associés aux gays et aux lesbiennes ne se limitent ni aux pratiques sexuelles ni à l'institution conjugale. L'ouvrage se propose de mettre en lumière non seulement la manière dont la culture façonne la sexualité, mais aussi comment, à partir de ces sexualités minoritaires, s'élaborent en retour des cultures originales.
Section: 125 pages ; 19 cm.
Keywords: LGBTQIA2+; approches et analyses; communauté; cours; culture homosexuelle; discipline; europe; france; homosexualité; hétérosexisme; militance; premier cycle; régions géographiques; sciences humaines; sciences sociales; sexualité; sexualités minoritaires; soc2014; sociologie; systèmes d'oppressions; thématiques; études gaies et lesbiennes

Porno? Chic!: how pornography changed the world and made it a better place - McNair, Brian (Routledge, 2013)
Porno? Chic! examines the relationship between the proliferation of pornography and sexualised culture in the West and social and cultural trends which have advanced the rights of women and homosexuals. Brian McNair addresses this relationship with an analysis of trends in sexualised culture since 2002 linked to a transnational analysis of change in sexual politics and sex/gender relations in a range of societies, from the sexually liberalised societies of advanced capitalism to those in which women and homosexuals remain tightly controlled by authoritarian, patriarchal regimes. In this accessible, jargon-free book, Brian McNair examines why those societies in which sexualised culture is the most liberalised and pervasive are also those in which the socio-economic and political rights of women and homosexuals have advanced the most.
Section: xii, 188 p. : ill. ; 24 cm
Keywords: LGBTQIA2+; approches et analyses; communication; cours; discipline; droits des femmes*; féminisme pop; identités LGBTQIA2+; justice sociale; premier cycle; queer; sciences humaines; sciences sociales; sex1911; sexualité; thématiques; études culturelles

Ethnic, Gender, and Acculturation Influences on Sexual Behaviors - Meston, Cindy M.; Ahrold, Tierney (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2010)
Much research has been conducted on ethnic differences in sexuality, but few studies have systematically assessed the importance of acculturation in sexual behavior. The present study assessed general differences in normative sexual practices in healthy Euro-American, Asian, and Hispanic populations, using measures of acculturation to analyze the relative effects of heritage and mainstream cultures within each group. A total of 1,419 undergraduates (67% Euro-American, 17% Hispanic, 16% Asian; 33% men, 67% women) completed questionnaires which assessed sexual experience and causal sexual behaviors. In concordance with previous studies, Asians reported more conservative levels of sexual experience and frequency of sexual behaviors, fewer lifetime partners, and later ages of sexual debut than Euro-American or Hispanic counterparts. Hispanic reported sexual experiences similar to that of Euro-Americans. There was a significant interaction between mainstream and heritage acculturation in predicting number of lifetime sexual partners in Asian women such that the relationship between heritage acculturation and casual sexual behavior was stronger at lower levels of mainstream acculturation. On the other hand, in Hispanic men, higher levels of mainstream acculturation predicted more casual sexual behavior (one-time sexual encounters and number of lifetime sexual partners) when heritage acculturation was low but less casual sexual behavior when heritage acculturation was high. These results suggest that, for sexual behavior, Hispanic men follow an “ethnogenesis” model of acculturation while Asian women follow an “assimilation” model of acculturation.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexualité; thématiques; états-unis